2015
DOI: 10.18632/oncotarget.6728
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the epithelial to mesenchymal transition and metastasis by Raf kinase inhibitory protein-dependent Notch1 activity

Abstract: Raf kinase inhibitory protein (RKIP), an endogenous inhibitor of the extracellular signal-regulated kinase (ERK) pathway, has been implicated as a suppressor of metastasis and a prognostic marker in cancers. However, how RKIP acts as a suppressor during metastasis is not fully understood. Here, we show that RKIP activity in cervical and stomach cancer is inversely correlated with endogenous levels of the Notch1 intracellular domain (NICD), which stimulates the epithelial to mesenchymal transition (EMT) and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 51 publications
0
23
0
1
Order By: Relevance
“…Once the metastasis occurred in distant organs, the survival rate and prognostic effect for cancer patients will be greatly reduced. The molecular events for metastasis are as follows: 1) the dysregulation of metastasis related genes, such as Ras, Mtsl, Nm23, TIAM-1, KAI1/CD82, RKIP, Kiss1, BRMS1, RhoGDI, MKK4, Drg-1 and so on [ 18 21 ]; 2) the abnormal expression of cell adhesion molecules, such as Integrins, Cadherins, Selectins, ICAM-1, VCAM-1, CD44 and so on [ 22 24 ]; 3) the abnormal expression of protein degrading enzymes, such as MMPs, t-PA, u-PA, Heparinase and so on [ 25 ]; 4) the over activation of tumor angiogenesis, and the key factors involved in this process including VEGF, bFGF, CD105 and so on [ 26 ]; 5) the imbalance of immune system states, and the major immune cells involved in anti-cancer immunity including NK cells, CTL cells, mononuclear macrophage cells, TIL cells and so on [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once the metastasis occurred in distant organs, the survival rate and prognostic effect for cancer patients will be greatly reduced. The molecular events for metastasis are as follows: 1) the dysregulation of metastasis related genes, such as Ras, Mtsl, Nm23, TIAM-1, KAI1/CD82, RKIP, Kiss1, BRMS1, RhoGDI, MKK4, Drg-1 and so on [ 18 21 ]; 2) the abnormal expression of cell adhesion molecules, such as Integrins, Cadherins, Selectins, ICAM-1, VCAM-1, CD44 and so on [ 22 24 ]; 3) the abnormal expression of protein degrading enzymes, such as MMPs, t-PA, u-PA, Heparinase and so on [ 25 ]; 4) the over activation of tumor angiogenesis, and the key factors involved in this process including VEGF, bFGF, CD105 and so on [ 26 ]; 5) the imbalance of immune system states, and the major immune cells involved in anti-cancer immunity including NK cells, CTL cells, mononuclear macrophage cells, TIL cells and so on [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was demonstrated that RKIP acts as a physiological inhibitor of NOTCH1, a major player in EMT and metastases [98]. Using H1299 cells, transfected to overexpress RKIP, the authors demonstrated that RKIP directly interacts with the full-length of NOTCH1, preventing its proteolytic cleavage and NICD release (Figure 1), decreasing EMT markers like Vimentin, N-cadherin and Snail.…”
Section: Rkip and Lung Cancer: Literature Reviewmentioning
confidence: 99%
“…Using H1299 cells, transfected to overexpress RKIP, the authors demonstrated that RKIP directly interacts with the full-length of NOTCH1, preventing its proteolytic cleavage and NICD release (Figure 1), decreasing EMT markers like Vimentin, N-cadherin and Snail. As a consequence, the migratory and invasive capacity of the cells also decreased, a phenotype that was reverted in vivo by RKIP knockdown in A549 cells [98].…”
Section: Rkip and Lung Cancer: Literature Reviewmentioning
confidence: 99%
“…136 RKIP-dependent Notch1 deactivation and cytoplasmic sequestration repress the expression of Notch1 target genes such as CDH2 , SNAI1 , and VIM in hypoxic conditions. 36 RKIP’s capacity to counteract the prometastatic effect of hypoxia and pro-EMT protein expressions highlights its role as a metastasis suppressor. 137 Previous reports also described a potential for RKIP to suppress cancer cell stemness via regulation of stem cell factors Oct4, Sox2, KLF2, and Nanog.…”
Section: Raf-1 Kinase Inhibitory Proteinmentioning
confidence: 99%
“…3234 Similar interactions with other proto-oncogenes [i.e., Notch1 and melanoma differentiation–associated gene-9 (MDA-9)] reiterate the attenuation of EMT in cells expressing high levels of RKIP. 35,36 Given RKIP’s eponymous function in the Ras/Raf/MEK signaling axis and the characterization of various nodes of convergence between the MAPK pathway and the PI3K/Akt/mTOR pathway, it makes sense that RKIP should directly or indirectly influence autophagic activity in cancer cells. 37 Indeed, it was recently shown that RKIP acts as a gatekeeper of autophagy by binding to LC3, an essential protein in autophagosome formation, thus halting autophagy.…”
Section: Introductionmentioning
confidence: 99%